Epidemiology and dermatological comorbidity of seborrhoeic dermatitis: population‐based study in 161 269 employees. (17th July 2019) - Zander, N.; Sommer, R.; Schäfer, I.; Reinert, R.; Kirsten, N.; Zyriax, B.‐C.; Maul, J.‐T.; Augustin, M.
Summary: Background: Seborrhoeic dermatitis is a common but epidemiologically poorly researched chronic skin disease. Objectives: To characterize the prevalence and dermatological comorbidity of seborrhoeic dermatitis in Germany. Methods: In the course of voluntary company skin checks, full‐body examinations were carried out in more than 500 companies by experienced dermatologists and documented electronically. Results: In total, 161 269 participants were included (men 55·5%, mean age 43·2 ± 10·9 years). Seborrhoeic dermatitis was identified in 3·2% (men 4·6%, women 1·4%). A significant difference was found between age groups (2·0% in < 35; 3·6% in 35–64; 4·4% ≥ 65 years). The most frequent concomitant skin conditions were: folliculitis [17·0%, 95% confidence interval (CI) 15·9–18·1], onychomycosis (9·1%, 95% CI 8·3–10·0), tinea pedis (7·1%, 95% CI 6·3–7·8), rosacea (4·1%, 95% CI 3·6–4·7), acne (4·0%, 95% CI 3·4–4·5) and psoriasis (2·7%, 95% CI 2·3–3·2). Regression analysis revealed the following relative dermatological comorbidities when controlling for age and sex: folliculitis [odds ratio (OR) 2·1, 95% CI 2·0–2·3], contact dermatitis (OR 1·8, 95% CI 1·1–2·8), intertriginous dermatitis (OR 1·8, 95% CI 1·4–2·2), rosacea (OR 1·6, 95% CI 1·4–1·8), acne (OR 1·4, 95% CI 1·2–1·7), pyoderma (OR 1·4, 95% CI 1·1–1·8), tinea corporis (OR 1·4, 95% CI 1·0–2·0), pityriasis versicolor (OR 1·3, 95% CI 1·0–1·7) and psoriasis (OR 1·2, 95% CI 1·0–1·5). Conclusions: Seborrhoeic dermatitis is a common disease, which is more prevalent in men and older people, and it has an increased rate of dermatological comorbidity. However, absolute differences in the prevalence of comorbidities are small and negligible. Nevertheless, the findings underline the need for integrated, complete dermatological diagnostics and therapy. Abstract : What's already known about this topic? Seborrhoeic dermatitis is a multifactorial skin disease with endogenous and exogenous predisposing factors. It is one of the more common skin diseases, and is estimated to affect between 1% and 8% of the general adult population. The prevalence of seborrhoeic dermatitis is higher among men and elderly people. Seborrhoeic dermatitis is associated with systemic diseases. What does this study add? Robust data on the epidemiology of seborrhoeic dermatitis on a population‐based level. Data on dermatological comorbidity; seborrhoeic dermatitis seems to be strongly associated with fungal and bacterial diseases and is a possible pathogenetic cofactor in the development of infectious skin diseases. Integrated, complete dermatological diagnostics and therapy are recommended. Linked Comment: Andersen and Egeberg. Br J Dermatol 2019; 181 :659 . Plain language summary available online Respond to this article